Isolates, antimicrobial susceptibility profiles and multidrug resistance of bacteria cultured from samples collected from sheep in New Zealand (2003–2016). Issue 1 (2nd January 2021) - Riley, CB; Pfeffer, H; MacLachlan, C; Wakeford, L; Gibson, IR; Benschop, J; Lawrence, KE
ABSTRACT: Aim: To describe the common species, antimicrobial susceptibility and multidrug resistance (MDR) of bacteria cultured from samples submitted to veterinary diagnostic laboratories from sheep in New Zealand between 2003 and 2016. Methods: Bacterial culture and antimicrobial susceptibility test data from June 2003 to March 2016 for animals identified as sheep were obtained from two commercial veterinary diagnostic laboratories in New Zealand. Submission information included animal signalment, geographic origin, specimen description, the organisms cultured, and where available, antimicrobial susceptibilities of the isolates. MDR was defined as any isolate with resistance to ≥3 antimicrobial classes. Results: There were 1, 971 unique laboratory submissions, yielding 2, 188 isolates. Of the 1, 971 submissions, the most commonly represented breeds were Romney (933; 47.3%), Romney cross (264; 13.4%), and Coopworth (197; 10.0%), and there were more submissions from females (1, 006; 51.0%) than males (184; 9.3%). Most submissions were from Canterbury (549; 27.9%), Southland (471; 23.9%), and Manawatu-Wanganui (272; 13.8%) regions. Other signalment data were inconsistently described. Submitted samples most commonly originated from the gastrointestinal tract (852; 43.2%), faeces (378; 12.1%), or liver (146; 7.4%). Of the 2, 188 isolates, 1, 771 (80.9%) were identified by species and 247 (11.4%) by genus, with the most common isolates being Salmonella spp. (880; 40.2%), Campylobacter spp. (408; 18.6%), Listeria spp. (140; 6.4%) and Yersinia spp. (113; 5.2%). Susceptibility results were available for 117/2, 188 (5.3%) isolates from 51/1, 971 (2.6%) submissions. No antimicrobial susceptibility data were available for Salmonella spp., Campylobacter spp., Listeria spp. or Yersinia spp. Overall for the isolates tested, susceptibility to the fluoroquinolones and tetracyclines was greatest, and MDR was found in 24/117 (20.5%) isolates. MDR was a more frequent finding for Enterococcus spp., Bacillus spp., and Proteus mirabilis, but was infrequent in isolates of Staphylococcus aureus, alpha-haemolytic streptococci, Escherichia coli or Enterobacter spp. Conclusions and clinical relevance: This is the first report on antimicrobial susceptibility and MDR for isolates from laboratory submissions from sheep in New Zealand. The low numbers of isolates submitted for antimicrobial susceptibility testing during the period studied mean that these findings provide limited insights into antimicrobial resistance in this population, and highlight the need to address significant gaps in our understanding of why veterinarians do not more frequently submit samples from sheep for bacterial culture and susceptibility testing. Abbreviation: AMR: Antimicrobial resistance; MDR: Multidrug resistance